2019
DOI: 10.1088/1757-899x/582/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Material and technical support of the enterprises of the agro-industrial complex of the Omsk region management and certification of the technical component of the production processes in crop production

Abstract: The management of a modern enterprise of the agro-industrial complex should cover all aspects of the production of the main types of products produced. In this concept in modern economic conditions it is necessary to include not only economic indicators and ways of selling finished products, but also the use of modern technologies, production safety for the environment and people. Improvement of technologies for obtaining crop production is impossible without updating the equipment used for the mechanization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The change in the availability factor of tractors depending on the period of operation (Fig. 1) (the ratio of the number of serviceable to the listed number) [3] depends on their aging, and the obtained aging coefficients by years of operation can be used to form the aging function. It is clear that the user of the machine already from the second year of its operation can do little to ensure a high serviceability of the tractor.…”
Section: Research Resultsmentioning
confidence: 99%
“…The change in the availability factor of tractors depending on the period of operation (Fig. 1) (the ratio of the number of serviceable to the listed number) [3] depends on their aging, and the obtained aging coefficients by years of operation can be used to form the aging function. It is clear that the user of the machine already from the second year of its operation can do little to ensure a high serviceability of the tractor.…”
Section: Research Resultsmentioning
confidence: 99%
“…Studies conducted in a number of regions of the country revealed the following reasons of poor quality of field work [2,3,6]:…”
Section: Introductionmentioning
confidence: 99%
“…;Redreev et al, 2017;Myalo et al, 2018;Galiev et al, 2018;Redreev et al, 2018;Gupta et al, 2019;Hrytsaienko et al, 2019;Myalo et al, 2019;Redreev et al, 2020;Galiev et al, 2020;Elhaki and Shojaei, 2020;de Araujo Zanella et al, 2020;Daum et al, 2021. Tractor maintenance Selection of the best maintenance alternative in maintenance planning of machines, selection of the most appropriate multi-criteria decision-making (MCDM) model to evaluate each alternative according to a set of criteria; It is a multicriteria decision making problem. In the methodology section, fuzzy numbers and fuzzy AHP used in the study and its application steps are given.…”
mentioning
confidence: 99%